Nanochitosan from Manufacture Shells of Mud Crab (Scylla sp.) and Its Application as Acne Patch - Luthfiyana, Novi; Ratrinia, Putri Wening; Nusaibah, Nusaibah; Nisa, Mutia Khoirun (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2024)
Chitosan is a potential raw material for marine cosmetics with antibacterial,anti-inflammatory properties and can stimulate collagen synthesis in theskin. This research aimed to obtain nano-sized chitosan (nanochitosan) frommud crab (Scylla sp.) shells and apply it as a cosmetic acne patch. Theparameters used to characterize nanochitosan are particle size, polydispersityindex, zeta potential and morphology. Meanwhile, the parameters of the Acnepatch produced are characterized by physical appearance and ance bacterialactivity. The results revealed that nanochitosan had an average size of 35.20±1.66 nm, the highest intensity of 11.70±1.25, polydispersity of 0.274±0.10,and zeta potential of 42.9±1.41 mV. The morphology of nanochitosan is in theform of broken rods, not hollow and irregular but uniform. Its elements includecarbon, oxygen, magnesium, aluminum, phosphorus, and calcium. The acnepatches resulting from the addition of 0 mg (K0), 50 mg (K1), 100 mg (K2),and 150 mg (K3) were opaque white, slightly transparent, smooth, elastic,and odorless. The thickness varies, namely, 0.014 ± 0.002 mm (K0), 0.017 ±0.002 mm (K1), 0.022 ± 0.004 mm (K2), and 0.031 ± 0.005 mm (K3). Theweight variations were 0.019 ± 0.001 mg (K0), 0.026 ± 0.005 mg (K1), 0.033± 0.002 mg (K2), and 0.047 ± 0.013 mg (K3). The moisture loss varied,namely, 7.525 ± 0.054% (K0), 3.201 ± 0.487% (K1), 2.741 ± 0.279% (K2), and2.017 ± 0.290% (K3). Acne patches K1, K2, and K3 were proven to be able toinhibit the activity of acne bacteria Propionibacterium acnes (9.5 ± 0.25 mm,10.67 ± 0.76 mm, and 9.17 ± 0.76 mm), Staphylococcus epidermidis (9.33 ±1.15 mm, 13.67 ± 2.02 mm, and 8.67 ± 1.89 mm), and S. aureus (10.33 ±0.25 mm, 11.83 ± 0.76 mm, and 8.66 ± 0.76 mm). This research succeededin obtaining chitosan from crab shells (Scylla sp) in nano size and acnepatches with the addition of nanochitosan effectively inhibited the growth ofacne bacteria.